A PROSPECTIVE STUDY OF FUNCTIONAL OUTCOME OF HOFFA FRACTURE TREATED WITH CANNULATED CANCELLOUS SCREWS, HERBERT SCREWS AND BUTTRESS PLATES – A PROSPECTIVE OBSERVATIONAL COHORT STUDY. - Sahoo, Sarthak; Nayak, Manmatha; Sahoo, Radhakishan (Student's Journal of Health Research Africa, 2025)
Background The three categories of partial articular fractures that make up distal femur AO type 33 B fractures are coronal split fracture, medial condyle fracture, and sagittal lateral condyle fracture. The rate of damage or the degree of osteoporosis influences the likelihood of a distal femur fracture. Objectives Examining the functional results of Hoffa fractures—coronal plane fractures of the femoral condyle—treated with buttress plates, cannulated cancellous screws, and Herbert screws is the goal of this study. Materials and Methods The orthopedic department of Srirama Chandra Bhanja (SCB) Medical College in Cuttack, Odisha, India, carried out this prospective study to examine the functional results of Hoffa fractures treated with buttress plates, cannulated cancellous screws, and Herbert screws. The research was conducted from June 2022 to May 2024. Results The study included 20 patients with an average age of 30.25 ± 7.01 years, predominantly male and manual laborers. Right-sided Hoffa fractures were more common, with Type I fractures and lateral condylar involvement being the most frequent. Male competitors made up 14 (70%), while female participants made up 06 (30%). 4.15±1.66 days passed between the injury and operation. The mean radiological union time was 2.3 ± 1.49 months, and the mean functional Knee Society Score was 80.45 ± 15.01. Complications were minimal, with infection in 10% and delayed union in 5% of cases. Conclusion Hoffa fractures are most frequently observed in male young adults and are mostly caused by automobile accidents. According to the results, anatomical factors also suggest that the lateral condyle sustains injuries more frequently than the medial condyle. Interestingly, every instance in this study was identified by X-ray and verified by CT scans, indicating that careful monitoring of X-rays by themselves can successfully detect Hoffa fractures. Recommendation Early intervention and tailored surgical approaches may improve Hoffa fracture outcomes.